(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The research dealt with the effect of the tax examiner’s efficiency in detecting tax evasion, as the research problem dealt with tax evasion, especially in Iraq, for many reasons and factors, including those related to tax administration represented in administrative corruption and the complexity of procedures in the tax accounting process and failure to achieve justice in the tax treatment, including the taxpayer himself, as he tries to evade for reasons Related to the level of tax awareness, loss of confidence in the tax administration, and reasons related to the state’s inability to manage the services file well and its ability to achieve the set goals, This reflected negatively on the emergence of some of the consequences of that, which are represented in the decrease in treasury revenues from its most important internal sources, loss of confidence between taxpayers and the tax administration, as well as the emergence of activities in which tax evasion is easy due to the difficulty of the process of listing those activities in addition to the state’s inability to invest in development projects They are in the interest of society and influence the level of competition between economic projects and burden the state with the interest resulting from loans to meet the shortage of revenues.